2015
DOI: 10.1007/s00380-015-0703-z
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of aortic complications in bicuspid aortic valve versus Marfan syndrome: relevance for therapy?

Abstract: Patients with bicuspid aortic valve (BAV) and patients with Marfan syndrome (MFS) are more prone to develop aortic dilation and dissection compared to persons with a tricuspid aortic valve (TAV). To elucidate potential common and distinct pathways of clinical relevance, we compared the histopathological substrates of aortopathy. Ascending aortic wall biopsies were divided in five groups: BAV (n = 36) and TAV (n = 23) without and with dilation and non-dilated MFS (n = 8). General histologic features, apoptosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 36 publications
5
26
0
Order By: Relevance
“…Diameters of the ascending segment of the aorta were larger in ever-pregnant women with bicuspid aortic valve disease than with Marfan syndrome, whereas more distal segments of the aorta were more dilated in ever-pregnant women with Marfan syndrome than with bicuspid aortic valve disease. Previous investigations confirmed that the anatomic site of major aortic pathology was distinct in both entities and showed that the maximal aortic dilatation occurred at the ascending aorta in individuals with bicuspid aortic valve disease [37,38]. In accordance with the literature, we found coarctation of the aorta only with bicuspid aortic valve disease but not with Marfan syndrome [39], and identified mitral valve prolapse only with Marfan syndrome but not with bicuspid aortic valve disease [40].…”
Section: Discussionsupporting
confidence: 91%
“…Diameters of the ascending segment of the aorta were larger in ever-pregnant women with bicuspid aortic valve disease than with Marfan syndrome, whereas more distal segments of the aorta were more dilated in ever-pregnant women with Marfan syndrome than with bicuspid aortic valve disease. Previous investigations confirmed that the anatomic site of major aortic pathology was distinct in both entities and showed that the maximal aortic dilatation occurred at the ascending aorta in individuals with bicuspid aortic valve disease [37,38]. In accordance with the literature, we found coarctation of the aorta only with bicuspid aortic valve disease but not with Marfan syndrome [39], and identified mitral valve prolapse only with Marfan syndrome but not with bicuspid aortic valve disease [40].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, Pham et al found BAV patients, which have been structurally and mechanically linked to MFS patients (13,14,23), to have significantly more isotropic aortic tissue than other AsAA patients, as also found in MFS patients in the current study (24). Pham also found a trend of age-related thickening in BAV tissue, agreeing with our MFS findings.…”
Section: Aneurysmal Stiffeningsupporting
confidence: 92%
“…Phillippi with Gleason and Vorp at University of Pittsburgh further characterized the medial matrix remodeling of the BAV aorta and found unique patterns as compared to TAV patients(74). Grewal and co-workers compared the histopathology of BAV, TAV, and Marfan aortic tissue and found both similarities and differences between all three groups with respect to parameters of matrix remodeling and vascular smooth muscle markers(75). The complexity of the histopathology remains high and it is not clear what molecular pathways are unique to the BAV aorta.…”
Section: Cellular and Molecular Mechanisms Of Bav Aortopathymentioning
confidence: 99%